Permanent Revolution — But Without Socialism? - Day, Richard B. (2013)
In his criticism of Witnesses to Permanent Revolution Lars Lih argues that, except for Trotsky, all the other authors included in our volume were proponents of a bourgeois-democratic revolution in permanence. The problem with this idea is that it misses the whole point of the debate, which was precisely to what extent bourgeois (peasant) and socialist (proletarian) elements would be combined in the coming revolution. Philosophically, it displays a lack of dialectics in attempting to force the law of identity (either a socialist or a bourgeois democratic revolution) upon a historical event which was basically a combination of two diffferent historical phenomena: a jacquerie and a urban-based working-class revolution.